Enhancing the rate of anaerobic hydrolysis of organic solids - Tan, Sheau Maan. (2011)
Anaerobic treatment of municipal wastewater has the potential to become as popular as aerobic treatment by virtue of its many advantages. However, hydrolysis of suspended solids present in municipal wastewater is the rate limiting step in the biodegradation process. In this project, the feasibility of enzyme augmentation to increase hydrolysis rate was studied. Temperature, pH and enzyme concentration were among the factors investigated in determining the optimum condition for enzymatic hydrolysis. A 23 full factorial design with center points was employed in the experimental design. The investigated temperature, pH and enzyme concentration ranges were 5—9, 25—35°C, and 0—33.3% v/v, respectively. The cumulative biogas volume are the highest for pH5 at 35°C with 33.3% v/v enzyme and pH7 at 30°C with 16.6% v/v enzyme (center point condition). Biogas composition (CO2: CH4 = 0.22:0.78) showed that center point condition is the most suitable condition for the enzyme augmented process. The center point condition is also more economically practical due to lower enzyme dosage and temperature besides consistently lowest final SCOD concentration. Batches with enzyme addition generally have higher total biogas volume produced. As the experiments were carried out using synthetic wastewater, further work is required to validate the experiment results using real wastewater. The fate and location of added enzyme necessitate further characterization for activity conservation.